2017
DOI: 10.1038/s41598-017-16344-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of circular RNAs in prenatal and postnatal pituitary glands of sheep

Abstract: Circular RNAs (circRNAs) are a class of animal non-coding RNAs and play an impor-tant role in animal growth and development. However, the expression and function of circRNAs in the pituitary gland of sheep are unclear. Transcriptome profiling of circRNAs in the pituitary gland of sheep may enable us to understand their biological functions. In the present study, we identified 10,226 circRNAs from RNA-seq data in the pituitary gland of prenatal and postnatal sheep. Reverse transcription PCR and DNA sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…The expression of circRNAs has been appropriately correlated with an abundance of host genes in different animal tissues [52][53][54][55] , such as oar_circ_0003451 and TTN, and oar_circ_0005250 and MYH7 may play important roles in muscle development and growth 22 ; circRNA8077 and CRIM1, as well as circRNA3314 and TMEM159 play vital roles in the development of the receptive endometrium 56 . The host genes of circRNAs are involved in regulating hair traits, and these circRNAs may be considered as a possible factor regulating cashmere fineness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of circRNAs has been appropriately correlated with an abundance of host genes in different animal tissues [52][53][54][55] , such as oar_circ_0003451 and TTN, and oar_circ_0005250 and MYH7 may play important roles in muscle development and growth 22 ; circRNA8077 and CRIM1, as well as circRNA3314 and TMEM159 play vital roles in the development of the receptive endometrium 56 . The host genes of circRNAs are involved in regulating hair traits, and these circRNAs may be considered as a possible factor regulating cashmere fineness.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, many studies have demonstrated that circRNAs contribute to the generation of cancer 18,19 , regulate gene expression in many biological processes, and participate in the occurrence and development of various diseases 20 . In a study by Li et al identified 6,113 circRNAs from muscles of sheep by RNA-seq 21 , and a total of 10,226 circRNAs were detected from pituitary glands of sheep by RNA-seq 22 . Zheng et al revealed that circRNAs can act as a microRNA sponge to isolate microRNA by competing with targeted mRNA 23 .…”
mentioning
confidence: 99%
“…The signal of a two-circRNA was found could predict tumor recurrence in clinically non-functioning pituitary adenoma [123]. Another study determined that thousands of sheep genes could express circRNAs in the pituitary gland [124]. Regarding circRNA, we determined that numerous circRNAs interact with highly expressed miRNAs both in exosomes and pituitary that are involved in the biologic functions of the pituitary gland.…”
Section: Discussionmentioning
confidence: 91%
“…The pituitary gland is essential for mammalian reproduction and growth development owing to its function of GH, FSH, LH, and PRL hormone secretion. Micro RNA [50], circular RNA [51] and lncRNA [31] were performed in different stages of sheep pituitary, however, little research of lncRNA on immature and mature stage of male sheep pituitary have been explored. In our study, three-month-old and nine-month-old male sheep were considered to be immature and mature stages for further lncRNA identification in the pituitary, and our study provided the systematic description and differential expression profiles of lncRNA and mRNA in sheep pituitary.…”
Section: Discussionmentioning
confidence: 99%